PERKEMBANGAN PERTANIAN KOPI RAKYAT DI DESA MARGAMULYA KECAMATAN PANGALENGAN TAHUN 1990-2015: DARI TRADISIONAL KE SISTEM AGRIBISNIS - Widiana Widiana; Murdiyah Winarti; Tarunasena Ma'mur (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2017)
The object of this research is the development of coffee farming which once was traditional, now turned into modern agribusiness system, the effort of increasing harvest and the shifting of farming’s system on coffee are also giving contribution to economy-social life especially for the farmers’ society.  This research is emphasized on year 1990-2015, because at that period, there was a shifting in the farming system also the effort of increasing harvest at Margamulya village.  The aim of this research is to be involve in a farmer’s life who was developing the farming system with technology.  The method of this research is historical, which include heuristik, critics (external and internal), interpretation and graphical history.  The approach of this research is interdisciplinary concept of sociology, anthropology, economics, and farming especially agribusiness.  Concept which are taken from sociology are the society, social stratification, social mobility, farmer.  Concept which are taken from economics are occupation, income.  Also the concept which are taken from farming is agribusiness.  The writer is interested to have this theme because Margamulya Village is one of the finest coffee producer which is located at Pangalengan District-Bandung with agribusiness system.  The geographical area of Margamulya Village is very suitable to be developed as a farming area which is the economic source of their people.  Meanwhile, the usage of forest area as farming vegetable’s ones cause several damages that lead to conflict between the forest worker and the farmer in 1998.  To solve this conflict, there was a discussion which produce an agreement that are beneficial for both parties, which is changing commodity.  Changing commodity from vegetables to coffee.  The traditional coffee farming which was pioneered at 1990 only covered the main necessities of the farmer because of its low income, hence the interest of developing coffee was lacked.  With the agreement between the forest worker and the famer, coffee farming then developed into agribusiness system on 1998 which influenced to the increased of the harvest, in quantitiy also quality.  The shifting of the farming system that pioneered by the farmer’s desire and supported well by the government are very influencing to the success of farming business which led to the wealth of the farming’s society.